3D Metasurfaces: Rapid Bending Origami in Micro/Nanoscale toward a Versatile 3D Metasurface (Laser Photonics Rev. 14(1)/2020). Issue 1 (8th January 2020) - Pan, Ruhao; Li, Zhancheng; Liu, Zhe; Zhu, Wei; Zhu, Liang; Li, Yunlong; Chen, Shuqi; Gu, Changzhi; Li, Junjie
Abstract : In article number 1900179, Junjie Li, Changzhi Gu, and co‐workers propose a rapid bending origami method for the fabrication of 3D bending micro/nano‐configurations with diversiform geometries based on the stress induced by FIB global irradiation. This method is applied to design and fabricate a 3D bending metasurface with bended nano‐cantilevers as an asymmetric mirror to realize strong unidirectional reflectionless effect with high reflection efficiency of 56% due to the asymmetric resonance, providing more opportunities and options for various functional devices based on 3D configurations.